ANALISIS PENGARUH RASIO KEUANGAN TERHADAP PERTUMBUHAN LABA PADA INDUSTRI ROKOK YANG TERDAFTAR DI BURSA EFEK INDONESIA - Sumarno Dwi Saputra, Sayekti (Universitas Slamet Riyadi, 2015)
Purpose of this research to analyze effect current ratio, debt to equity ratio, net profit margin, return on asset and price earning ratio on earnings growth partially and simultaniously. Research object are the cigarette industry listed in Indonesia Stock Exchange. This type of data is quantitative data and qualitative data. Source of data use secondary data. Population of this research are 4 cigarette company with total sampling technique. Collecting data used documentation and literature. Techniques analysis used multiple linear regression. The results of the analysis that current ratio no significant effect on earnings growth. Debt to equity ratio no significant effect on earnings growth. Net profit margin has significant effect on earnings growth. Return on assets has significant effect on earnings growth. Price earnings ratio has significant effect on earnings growth. Current ratio, debt to equity ratio, net profit margin, return on assets and the price earnings ratio influence on earnings growth simultaniously. Keywords: financial ratios, earnings growth